Restoration of degraded forest using native and exotic species: Investigation on soil productivity and stand quality (Case study: Chamestan-Mazandaran province) - Razieh Rafiei Jahed; Mohammad Ali Fakhari; Jamshid Eslamdoust; Mahboubeh Fashat; Yahya Kooch; Seyyed Mohsen Hosseini (تحقیقات جنگل و صنوبر ایران, 2017)
After 20 years, the effects of five plantations of Acer velutinum Boiss., Cryptomaria japonica D. Don., Cupressus sempervirens L. var. horizontalis (Mill.) Gord., Pinus taeda L.and mixed stand on soil fertility and quality of the stands were investigated and compared with natural forest to determine the appropriate species for planting in low land of Hyrcanian forests. Five 400 m2 plots were selected randomly- systematic in each stand. Quantitative and qualitative characteristics were recorded. Also, within each plot soil in 0-15, 15-30 and 30-45 cm depths were sampled. The results showed significant effect of reforestation on pH, EC, bulk density, organic carbon, total nitrogen, phosphorus and carbon sequestration in the soil. According to the result, P. taedahas the highest pH (4/6) while A. velutinum has the lowest pH (5.5), natural forest stand has the highest (18/0 ds/m) whereas C. japonica has the lowest (06/0 ds/m) EC. Pinus taeda has the highest organic carbon content (1.29%) and total nitrogen (0.36%) but the natural forest has the lowest amount of organic carbon (1.03%) and total nitrogen (0.08%). The mixed stand has the highest phosphorus (1.9 g/kg) and C. japonica has the lowest one (1.8 g/kg). The A. velutinum has the greatest (292830 Mg/ha) while the natural forest has the lowest (223920 Mg/ha) amount of carbon sequestration. The results showed the conifer stands have been more successful in terms of tree quality characteristic while broadleaf stands were more successful in the quantitative characteristic. Finally, it can be claimed that broadleaves stands were more successful in compare with conifer stands.